Three dimensional geometry of the bushveld complex derived from potential field modelling - Cole, Janine (My University, 2018)
Two dimensional gravity models and a few magnetic models limited to short profiles in the eastern sections of the BC have been used to propose conflicting geometries for the Rustenburg Layered Suite (RLS), especially between the western and eastern lobes; one school argued for completely separate intrusions, while the other proposed that the outcropping lobes are connected at depth. These competing models suggest different emplacement models. They provide a valuable starting point, but, 2.5D potential field modelling is not well suited to modelling complex three dimensional geology. Also, in previous work the magnetics or only the gravity data were modelled independently. Here I present the first full three dimensional potential field forward modelling of the central and southern Bushveld Complex (BC) which has been used to test the geometry of the Bushveld Complex in areas obscured by younger geological cover. Both gravity and magnetic data have been used to develop a geological model that is consistent with both data sets. Joint 3D modelling of regional gravity and magnetic data combined with published crustal thickness models derived from broadband seismic tomography studies were used to create a 3D model of the central and southeastern sections of the BC, as well as the southern part of the northern lobe. Eight downhole logs with more than 730 000 new density and magnetic susceptibility measurements from the RLS were combined with existing data to determine values for Bushveld Complex lithologies that were used in the model. The 3D model has a complex geometry with thick continuous RLS in most of the western lobe, thinner RLS in the south-eastern lobe, but a disrupted RLS in the eastern lobe. Large domes of Transvaal dolomite or thicker granites and granophyre in the eastern lobe interrupt the continuity of the RLS. The western and eastern lobes are therefore broadly connected, with major disruptions largely in the eastern lobe. However, they are not separate intrusions, but represent a single magma chamber affected by pre-existing and syn-magmatic updoming. The model includes the whole thickness of the crust and requires dense material at the crust mantle boundary. Thus, for the first time, I have imaged the remnants of magma staging chambers. The chambers, constrained by the extent of the diffuse crust-mantle transition as determined from teleseismic data, underlie the whole Bushveld Complex, but is thickest under the northern, south-eastern and western parts of the complex. I propose feeders that correlate with the chambers in the northern lobe near the large gravity high near Polokwane and in the south-eastern lobe.
A Thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2018
Keywords: Three-dimensional display systems; Geological modeling--Computer simulation